Processo de introdução de triagem auditiva neonatal em um hospital filantrópico de Belo Horizonte - Abreu, Ana Célia Pereira de (2007)
The early diagnosis of auditory deficiencies is one of the decisive factors for the better development of the language functions of a deficient child. It is during childhood that the neurological maturation occurs, thus favoring the development of the basic perceptive abilities, as well as of language itself. Given the importance the early auditory deficiency diagnosis, programmes of universal neonatal hearing screening have been proposed world-wide. With the aim of implementing a neonatal hearing screening programme that has an efficient protocol, this study describes the findings of a hearing screening programme conducted with 140 babies born at the Hospital Evangélico de Belo Horizonte in the period between April and June 2005, utilizing two forms of scheduling: hearing screening conducted 15 days after hospital release and hearing screening conducted immediately after hospital release. The methodology utilized in the study includes: anamnesis of the prenatal, neonatal and postnatal conducted through interviews with the mothers, hearing screening using Transient Evoked Otoacoustic Emissions, Distortion Product Otoacoustic Emissions and research of the Eye-Blink Reflex (EBR). Of the 228 (100%) babies born in this period at the hospital, of which 138 (65,7%) were born in April and 72 (34,3%) in June, 210 (92,1%) have been recruited to have the hearing screening test administered. In the April group hearing screening was scheduled for 15 days after hospital release and in the June group hearing screening was scheduled immediately after hospital release. Of the 210 (100%) babies recruited, 140 (66,6%) attended triage, of which 70 (50,7%) belonged to the 15-day group and 70 (97,2%) to the Release group. Of the 70 (100%) evaluated babies in the 15-day group, 6 (8,5%) have presented indicators of risk of auditory deficiency; and of the 70 (100%) evaluated babies in the Release group, 6 (8,5%) have also presented indicators of risk auditory deficiency. Of all the babies evaluated, 140 (100%) presented EBR. In the research of both the transient evoked and distortion product otoacoustic emissions, 2 babies (2,9%) of the 15-day group have failed the evaluation, and in the Release group 22 (31,4%) have also failed. The findings of this study have demonstrated that the failure rate of the 15-day group in the otoacoustic emission test is lower when compared to the rate of the Release Group, however the consent to the test went higher in this group, given that the ease of having the test performed at the moment of release does not require the mother to return to the hospital